2017
DOI: 10.1371/journal.pone.0178481
|View full text |Cite
|
Sign up to set email alerts
|

Viral etiologies in adult patients with encephalitis in Poland: A prospective single center study

Abstract: Encephalitis is a severe neurological syndrome associated with high morbidity and mortality as well as long-term neurological sequelae. Despite being an important public health problem, very few extensive population-based studies were conducted so far in the world and none in Central Europe. Altogether 114 consecutive patients meeting the initial criteria for encephalitis were enrolled at the Warsaw Hospital for Infectious Diseases between June 2012 and July 2015. Eighteen patients were secondarily excluded fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
3
11
0
1
Order By: Relevance
“…In spite of the small sample size, the finding of HSV-1 as the predominantly identified virus in this study was consistent with others from Vietnam [22], India [23], Norway [24], and Poland [25], while other studies in Vietnam [26] and Thailand [27] reported JEV as the most common identified viral cause of CNS infection. Furthermore, recent studies in China [28] and Italy [29] found EV as the primary identified viral pathogen causing CNS diseases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In spite of the small sample size, the finding of HSV-1 as the predominantly identified virus in this study was consistent with others from Vietnam [22], India [23], Norway [24], and Poland [25], while other studies in Vietnam [26] and Thailand [27] reported JEV as the most common identified viral cause of CNS infection. Furthermore, recent studies in China [28] and Italy [29] found EV as the primary identified viral pathogen causing CNS diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Fifth, MRI which is more sensitive than CT, was not performed under resource-limited healthcare settings. Sixth, the prevalence of etiological agents detected in this study might be low compared with other studies [25,26,28,29,47], possibly due to the different molecular tools used (pan-family vs virus-specific PCR/RT-PCR) and case selection methods (suspected CNS infection vs encephalitis/meningoencephalitis only). Seventh, with a small sample size, our conclusions on viral etiology might not be statistically significant.…”
Section: Discussionmentioning
confidence: 56%
“…Przyczyną zapalenia opon mózgowo-rdzeniowych i/lub mózgu mogą być różnorodne czynniki zakaźne, głównie bakteryjne i wirusowe, ale także grzyby i pierwotniaki. Klinicznie mogą również wynikać z czynników autoimmunologicznych i warunków paraneoplastycznych (1). Wśród zachorowań na zapalenie opon mózgowo-rdzeniowych i/lub mózgu, potwierdzonych badaniem laboratoryjnym najczęściej występują zachorowania wywołane przez Neisseria meningitidis i Streptococcus pneumoniae.…”
Section: Wstępunclassified
“…Clinically, they may also result from autoimmune factors and paraneoplastic conditions. (1) The incidence of meningitis and / or encephalomyelitis, confirmed by laboratory tests, is most often caused by Neisseria meningitidis and Streptococcus pneumoniae. Among viral neuroinfections, tick-borne encephalitis predominates.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 3 studies, none included comparison of serum- and CNS-derived virus. We conducted a study of 96 consecutive patients with diagnosis of encephalitis ( 18 ) in Poland during 2012–2015 to determine whether HPgV could be found in the CNS.…”
mentioning
confidence: 99%